Tactile Flipbook Magic: A multisensory framework for enhancing phonics decoding skills in primary education - Ana Zulianingrum; Sheila Wijayanti; Ajeng Ayu Ramadhanti; Naila Suryani (Community Empowerment, 2026)
Traditional learning methods often face difficulties in concretizing the abstract relationship between sounds and letters. This community service program addresses an important challenge in teaching foundational phonic decoding skills to early childhood learners at SD Angkasa 01 Halim Perdanakusuma. The purpose of this activity is to design, implement, and evaluate the impact of "Flipbook Magic," an interactive tactile medium, on students' decoding abilities and teachers' pedagogical competence. The methodology used follows a four-stage collaborative model, which includes needs analysis, collaborative medium creation process with teachers, direct implementation in grade II through co-teaching sessions, and evaluation with mixed methods (quantitative and qualitative). The results from the structured observation checklist showed a significant increase in students' decoding skills. The percentage of students able to blend CVC patterns independently increased from 20% to 80%, while 40% of students successfully blended target CVCC/CCVC patterns independently and another 40% succeeded with teacher assistance. Qualitatively, the use of this medium significantly increased student engagement and participation in learning. In addition, the applied mentoring model successfully empowered teachers, with more than 90% of teachers showing the ability to use the medium independently and integrate it into lesson plans. The program concludes that Flipbook Magic, combined with a partnership-based empowerment approach, is an effective strategy to improve early literacy learning. Therefore, schools are advised to adopt similar practice-based learning tools and collaborative professional development models to maintain sustainability and expand the improvement of phonics education.